Assessing the occurrence of soil improvement and its relationship to the dominant life form in the high mountains of Central Spain - Magaña Ugarte, R.; Gavilán, R.G.; Rubio, A. (Geoderma Regional, 2024)
Soil in mountainous regions is vital to the health and preservation of these unique and diverse ecosystems. In dry and semi-arid regions, vegetation patches play a crucial role in soil nutrient heterogeneity through continuous feedback with soils, acting as barriers to collect runoff water, sediments, and nutrients from bare soil regions. Soil amelioration, an enhancement of soil biogeochemical processes, results in the formation of “fertility islands,” the extent of which is contingent on the plant species in question, as well as nutrient dynamics and water availability. Here, we collected soil from across a two-peak altitudinal gradient in the Sierra de Guadarrama high-mountains, each peak featuring a different dominant vegetation type (herbs vs. cushion-like) to compare soil nutrients and properties between bare soil and vegetation-covered patches (microhabitats). Soil improvement was assessed in the microhabitats using the Relative Interaction Index (RII). Fertility islands were shown to be prevalent in high-mountain ecosystems, as soil quality and properties were higher beneath vegetation-covered regions than bare soils. There was a difference in RIIs between the transects, with greater soil improvement in the cushion-dominated transect than the herb-dominated one. Changes in nutrient levels were unrelated to patch successional stage, indicaing that plant generations may not shape the spatial variability of soil attributes. Instead, species variety or the presence of dominant clonal species increased soil nutrients and aggregate stability, highlighting the importance of root shape and high biomass in nutrient retention and soil reinforcement. Finally, our findings imply that the poor, shallow soils in the examined peaks, in comparison to other mountains, may account for the poor facilitative interactions. Competition for the scarce resources at these peaks may intensify as climate warms. Thus, while these plants may grow with minimum assistance under current climate circumstances, their associations may be especially vulnerable to climate change. •Our data validated “fertility islands” in these mountains by showing improved soil quality under vegetation patches than bare soils.•Plant patch specialist species improved soil ecology, compared to bare soils, by changing soil spatial heterogeneity.•Cushions' minor alteration of soil properties shows that soil quality can be improved regardless of the dominant plant life or elevation.•Cushions may offer mild amelioration due to the shallow soils and limited nutrient content along the gradient, which limit faciliative interactions